Tectonic inversion events in the western San Jorge Gulf Basin from seismic, borehole and field data - Navarrete Granzotto, César Rodrigo (2015)
The San Jorge Gulf Basin, located in Central Patagonia, has been interpreted as a Jurassic-Cretaceous rift basin that was later inverted mainly in its western sector. Consequently, the Bernardides System formed as a set of foreland contractional structures that constitute the core of the Patagonian broken foreland, exhuming continental deposits of the Cretaceous Chubut Group, 500 km away from the Pacific trench. In spite of the intense research done in the San Jorge Gulf Basin many aspects remain under discussion, particularly those regarding the age of uplift of the Bernárdides System. In order to unravel the tectonic evolution of the western San Jorge Gulf Basin (Río Mayo Sub-Basin), we analyzed subsurface information (2D and 3D seismic lines and oil wells) located in the western area of the basin and compared this with surface data of the southern Bernárdides System. Based on our interpretation, the western part of the basin could have been uplifted in a series of deformational events that began as early as late Early Cretaceous, related to the initial uplift of the Patagonian broken foreland, during the early stages of South Atlantic opening. Subsequent stages of tectonic reactivation identified in this system have selectively inverted previous extensional structures according to the variable direction of the greatest horizontal stress (σ1) acting at each time.